The Role Of Digital Literacy In Learning Financial Report Analysis For Students Of Class XI Beauty School - Margareta, Elisabeth; Nababan, Netty Winda Sari; Sembiring, Nanda; Munthe, Lesmita; Tamba, Noni Tiurmayanti (Jurnal Mamangan, 2023)
This study aims to analyze the Role of Digital Literacy in Learning Financial Report Analysis for Grade XI Beauty Students of Imelda Tourism Vocational School, Medan. This study uses a qualitative descriptive research type, which aims to describe in depth how the role of digital literacy affects learning financial report analysis for students. Based on the results of the study that has been conducted on the Role of Digital Literacy in Learning Financial Report Analysis for Grade XI Students of Imelda Tourism Vocational School, Medan, several things can be concluded as follows: as many as 70% of grade XI students show good digital literacy skills, marked by their ability to access, use, and explore financial information through digital media. Students have been able to use technological devices such as computers, the internet, and basic financial applications to support learning financial report analysis. Qualitative data from observations and interviews show that students with high levels of digital literacy have better abilities in analyzing financial reports, including reading financial reports, interpreting numerical data, and compiling simple reports. This shows a positive correlation between mastery of digital technology and achievement of economic learning outcomes. Although many students have utilized technology for educational purposes, there are still around 30% of students who predominantly use digital media only for entertainment such as playing games and social media. This shows that students' digital literacy is not fully directed at productive use for learning